Identification and pathogenicity of Lasiodiplodia theobromae causing dieback of table grapes in Peru - Rodríguez-Galvez, E.
Production of table grapes is a major export commodity in the region of Piura, one of the most important grape-production areas of Peru. Characteristic symptoms of Botryosphaeria dieback were observed in vineyards throughout this region. The aim of this study was to characterise the symptoms of dieback of table grapes; evaluate the incidence and prevalence of the disease; identify the aetiological agent and evaluate its pathogenicity and virulence. The disease was present in all vineyards surveyed but incidence varied with location. A botryosphaeriaceous fungus was isolated from symptomatic plants collected in five different vineyards in Piura. On the basis of morphological and cultural characters as well as phylogenetic analysis of the internal transcribed spacer region (ITS), and part of the translation elongation factor 1-α gene (EF1-α) the isolates were identified as belonging to the species Lasiodiplodia theobromae. Inoculation of cv. Red Globe plants confirmed the pathogenicity of the isolates and revealed differences in virulence among the isolates tested. This is the first report of L. theobromae as causal agent of dieback of table grapes in Peru, which represents a threat to Peruvian vineyards productivity and longevity.